The impact of oxaliplatin‐based chemotherapy for colorectal cancer on the autonomous nervous system. (17th July 2014) - Dermitzakis, E. V.; Kimiskidis, V. K.; Eleftheraki, A.; Lazaridis, G.; Konstantis, A.; Basdanis, G.; Tsiptsios, I.; Georgiadis, G.; Fountzilas, G.
<x xml:space="preserve">Abstract</x> Background The oxaliplatin (ΟΧΑ)‐based regimens FOLFOX and XELOX can cause peripheral neuropathy. It is unknown if ΟΧΑ, alone or in combination regimens, affects the Autonomous Nervous System (ANS). Accordingly, we evaluated the impact of ΟΧΑ‐based chemotherapy on the ANS. Methods We enrolled 36 patients with colorectal cancer, treated with adjuvant mFOLFOX6 or XELOX chemotherapy, and 22 healthy volunteers. For the assessment of ANS function, participants completed a questionnaire and underwent neurophysiological examination at three time points (baseline, 3–4 months and 6–8 months after the first chemotherapy cycle). ANS testing included assessment of the adrenergic cardiovascular function (orthostatic hypotension‐OH), parasympathetic heart innervation (ratio 30/15) and Sympathetic Skin Response (SSR). Results The values of the 30/15 ratio were significantly reduced at the two time point assessments compared to baseline (Wilcoxon signed ranks test, both P < 0.001), while patients had more often diastolic OH at the 6–8 month evaluation compared to baseline (P = 0.039). In contrast, SSR was not affected. The incidence of positive responses in the questionnaire assessing the subjective impact of symptoms attributable to ANS dysfunction was higher at the two time points compared to baseline (P = 0.036 and P = 0.020). Conclusions Oxaliplatin‐based chemotherapy is associated with significant effects on the adrenergic cardiovascular reaction and the parasympathetic heart innervation, whereas SSR remains untouched.